Negotiating the Transatlantic deal: focus on the EU's domestic constraints - Alina Alexoaei; Valentin Cojanu (CES Working Papers, 2017)
The paper focuses on emphasising the role that internal constraints and domestic political events play in designing the strategic behaviour and position of the EU in the negotiation process of The Transatlantic Trade and Investment Partnership - TTIP. The paper pursues a three-pronged approach in order to: (1) identify and define the set of domestic constraints, (2) assess their influence on EU's strategic position, and (3) suggest both available and desirable future courses of action to improve the negotiation outcome. The results should inform the approach towards the general structure of negotiations to be accomplished through a multi-level analysis: starting from a broad EU perspective on the deal, complemented by a disaggregated domestic level perspective that will emphasize EU members' position and interests in the agreement, as well as an industry/sector-based implications of each item on the negotiations agenda.
Keywords: 330; TTIP; negotiations; domestic factors; strategic game; European Union